Polemik Kebijakan Impor Limbah Non Bahan Berbahaya Dan Beracun Di Indonesia - MARTIN EKO PRIYANTO (Jurnal Penegakan Hukum Indonesia, 2021)
Indonesia is infamous as the largest waste producer with insufficient management. Based on the Data from the Central Statistics Agency shows that at least plastic waste in Indonesia reaches 64 million tons. Further the import of non-hazardous waste has become a polemic due to the fact that there has been smuggling of waste contaminated with B3 waste in the practice of importing waste in Indonesia which results in many environmental and social problems. Therefore, existing legal rules must be fully enforced to ensure environmental sustainability while fulfilling the needs of the national industry. With a conceptual approach, this study examines legal instruments and the accountability of parties involved in importing non-hazardous waste in Indonesia.